The solution to the equation 3a-7(3-a)=5 is a=13/5.
Let's solve for a in the equation:
3a-7(3-a)=5
We can solve the equation by rearranging the terms, distributing, combining like terms, adding/subtracting to both sides, dividing both sides by the same factor, and simplifying.
Steps to solve:
Rearrange terms:
3a-7(-a+3)=5
Distribute:
3a+7a-21=5
Combine like terms:
10a-21=5
Add/subtract to both sides:
10a-21+21=5+21
Simplify:
10a=26
Divide both sides by the same factor:
10a/10=26/10
Simplify:
a=13/5